Issue Information. Issue 1 (28th January 2022) - Unknown
Abstract : Cover : Confocal imaging is an important tool for plant developmental biology. A detailed and optimized procedure for the perturbation, dissection, mounting, and imaging of developing leaves by confocal microscopy, however, is lacking. In this issue, Linh and Scarpella address this limitation by providing a detailed protocol for the imaging of leaves and leaf primordia by confocal microscopy. The cover image shows an artistic representation, showing a snowflake arrangement of developing Arabidopsis leaves in which veins are marked by the expression of nuclear Yellow Fluorescent Protein (YFP). The image illustrates that leaf cells differentiate anew during the development of each leaf, that leaves are produced in abundance, and that they are easily accessible to visualization and perturbation. To visualize YFP expression levels, look‐up tables (LUTs) were used to assign specific colors to different levels of expression. Image provided by the authors.